2022
DOI: 10.7150/thno.72258
|View full text |Cite
|
Sign up to set email alerts
|

A surrogate marker for very early-stage tau pathology is detectable by molecular magnetic resonance imaging

Abstract: The abnormal phosphorylation of tau is a necessary precursor to the formation of tau fibrils, a marker of Alzheimer's disease. We hypothesize that hyperphosphorylative conditions may result in unique cell surface markers. We identify and demonstrate the utility of such surrogate markers to identify the hyperphosphorylative state. Methods: Cell SELEX was used to identify novel thioaptamers specifically binding hyperphosphorylative cells. Cell surface vimentin was identified as a potential binding target of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Aptamers are short strands of nucleic acid probes that recognize a target with high specificity and sensitivity, in this case hyperphosphorylated cells (Parekh et al, 2013). The selection of aptamers specific for the hyperphosphorylative state of the cell led us to two aptamers that bound cell-surface vimentin identified as the potential target differentially expressed on the surface of hyperphosphorylative cells (Parekh et al, 2022). To enable mMRI of prepathological state, targeted liposomal-Gd nanoprobes (TauX) using aptamers and a small molecule ligand to vimentin were fabricated and tested in vivo (Figure 11).…”
Section: Advances In Nanoprobes For Mmri Of Tau Pathologymentioning
confidence: 99%
See 4 more Smart Citations
“…Aptamers are short strands of nucleic acid probes that recognize a target with high specificity and sensitivity, in this case hyperphosphorylated cells (Parekh et al, 2013). The selection of aptamers specific for the hyperphosphorylative state of the cell led us to two aptamers that bound cell-surface vimentin identified as the potential target differentially expressed on the surface of hyperphosphorylative cells (Parekh et al, 2022). To enable mMRI of prepathological state, targeted liposomal-Gd nanoprobes (TauX) using aptamers and a small molecule ligand to vimentin were fabricated and tested in vivo (Figure 11).…”
Section: Advances In Nanoprobes For Mmri Of Tau Pathologymentioning
confidence: 99%
“…The rich experience using liposomal agents in clinical trials and the availability of FDA‐approved liposome‐based drug products make this platform particularly attractive for the development of clinically translatable mMRI agents. Liposome‐based gadolinium contrast agents have been investigated for mMRI of Alzheimer's disease (Badachhape et al, 2020; Parekh et al, 2022; Tanifum et al, 2016). Mechanistic and in vivo imaging studies have shown that covalently presented Gd‐chelates on liposome surface slow down rotational correlation times of gadolinium moieties, boosting T1 relaxivity, and transforming them into ultra‐sensitive T1‐based contrast agents (Ghaghada et al, 2009; Mulder et al, 2013).…”
Section: Nanoprobe Platforms For Molecular Imaging Of Alzheimer's Dis...mentioning
confidence: 99%
See 3 more Smart Citations